BMI and future risk for COVID-19 infection and death across sex, age and ethnicity: Preliminary findings from UK biobank. Issue 5 (September 2020) - Sattar, Naveed; Ho, Frederick K.; Gill, Jason MR.; Ghouri, Nazim; Gray, Stuart R.; Celis-Morales, Carlos A.; Katikireddi, S. Vittal; Berry, Colin; Pell, Jill P.; McMurray, John JV.; Welsh, Paul
Abstract: Aims: We examined the link between BMI and risk of a positive test for SARS-CoV-2 and risk of COVID-19-related death among UK Biobank participants. Methods: Among 4855 participants tested for SARS-CoV-2 in hospital, 839 were positive and of these 189 died from COVID-19. Poisson models with penalised thin plate splines were run relating exposures of interest to test positivity and case-fatality, adjusting for confounding factors. Results: BMI was associated strongly with positive test, and risk of death related to COVID-19. The gradient of risk in relation to BMI was steeper in those under 70, compared with those aged 70 years or older for COVID-19 related death (Pinteraction = 0.03). BMI was more strongly related to test positivity (Pinteraction = 0.010) and death (Pinteraction = 0.002) in non-whites (predominantly South Asians and Afro-Caribbeans), compared with whites. Conclusions: These data add support for adiposity being more strongly linked to COVID-19-related deaths in younger people and non-white ethnicities. If future studies confirm causality, lifestyle interventions to improve adiposity status may be important to reduce the risk of COVID-19 in all, but perhaps particularly, non-white communities. Highlights: BMI is strongly linked to risk for SARS-CoV-2 in hospital and COVID-19-related death among UK Biobank participants. These associations were stronger for individuals under 70 versus those over 70 years of age at time of pandemic. They were also stronger for non-whites (predominantly South Asians and Afro-Caribbeans), compared with whites.